Design of low voltage ring oscillator - JIANG Jin-guang; LI Tian-wang (Tongxin xuebao)
A new ring oscillator was proposed.To reduce the threshold voltage of PMOS transistor,a two stage ring oscillator was designed by forward biasing the bulk of the PMOS transistor.Simulation results show that the new ring oscillator can work at the very high frequency with a low supply voltage,and the output frequency of the proposed ring oscillator can range from 300MHz to 4GHz in 1V supply voltage.